Late accretion of Ceres-like asteroids and their implantation into the outer main belt - Takir, Driss; Neumann, Wladimir; Raymond, Sean N.; Emery, Joshua P.; Trieloff, Mario (Nature astronomy, 2023)
Low-albedo asteroids preserve a record of the primordial Solar System planetesimals and the conditions in which the solar nebula was active. However, the origin and evolution of these asteroids are not well constrained. Here we measured visible and near-infrared (about 0.5-4.0 μm) spectra of low-albedo asteroids in the mid-outer main belt. We show that numerous large (diameter >100 km) and dark (geometric albedo <0.09) asteroids exterior to the dwarf planet Ceres’ orbit share the same spectral features, and presumably compositions, as Ceres. We also developed a thermal evolution model that demonstrates that these Ceres-like asteroids have highly porous interiors, accreted relatively late at 1.5-3.5 Myr after the formation of calcium-aluminium-rich inclusions, and experienced maximum interior temperatures of <900 K. Ceres-like asteroids are localized in a confined heliocentric region between about 3.0 au and 3.4 au, but were probably implanted from more distant regions of the Solar System during the giant planet’s dynamical instability.
Gesehen am 21.02.2023